2017
DOI: 10.1002/jcp.26179
|View full text |Cite
|
Sign up to set email alerts
|

Blunting of estrogen modulation of cardiac cellular chymase/RAS activity and function in SHR

Abstract: The relatively low efficacy of ACE-inhibitors in the treatment of heart failure in women after estrogen loss may be due to their inability to reach the intracellular sites at which angiotensin (Ang) II is generated and/or the existence of cell-specific mechanisms in which ACE is not the essential processing pathway for Ang II formation. We compared the metabolic pathway for Ang II formation in freshly isolated myocytes (CMs) and non-myocytes (NCMs) in cardiac membranes extracted from hearts of gonadal-intact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…rMCP-1 and rMCP-5 were the predominant chymase isoforms in WKY and SHR while expression levels of all rMCPs were significantly lower in CMs from SHR. The current findings expand on our previous observation that OVX in WKY is associated with increased chymase enzymatic activity [23]through demonstrating that this effect is due to a robust increase in rMCP-1 and rMCP-5 mRNA levels in CMs of WKY. A comparatively modest increase in rMCP-1 in CMs was seen in OVX SHR, with no change in rMCP-5 with OVX.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…rMCP-1 and rMCP-5 were the predominant chymase isoforms in WKY and SHR while expression levels of all rMCPs were significantly lower in CMs from SHR. The current findings expand on our previous observation that OVX in WKY is associated with increased chymase enzymatic activity [23]through demonstrating that this effect is due to a robust increase in rMCP-1 and rMCP-5 mRNA levels in CMs of WKY. A comparatively modest increase in rMCP-1 in CMs was seen in OVX SHR, with no change in rMCP-5 with OVX.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies from our laboratory found that ovarian hormones regulate the expression and activity of cardiac rMCP-1 in the SHR [23], and that ovariectomy (OVX) augments cardiac chymase activity in both Wistar Kyoto rats (WKY) and SHR [23]. The present study was designed to identify: 1) other isoforms of rat mast cell serine proteases expressed in cardiomyocytes (CM); 2) which chymase isoforms correlate with indices of cardiac function and Ang II forming activity in the CM; and 3) the impact of ovarian hormone depletion on the expression of chymase isoforms in the CM.…”
Section: Introductionmentioning
confidence: 79%
“…ACE2 deactivation showed a robust correlation to the diastolic dysfunctional phenotype of SHRs and a modest relationship to worsening filling pressures in WKY rats after OVX. In a follow-up study to determine the exact role of estrogen status on ACE2 in isolated cardiomyocytes [21], we again found that ACE2 activity was higher in normotensive WKY rats, although this strain effect was independent of estrogen status. Indeed, loss of ACE2 has been shown to accelerate maladaptive remodeling after MI [71].…”
Section: Estrogen Regulation Of Ace2mentioning
confidence: 70%
“…Based on the growing evidence suggesting a sex-based difference in COVID-19 outcomes, an assessment of sexspecific hormone activity, particularly estrogen, in COVID-19 pathogenesis is warranted. Estrogen is known to modulate CVD risk and we [11] and others [18] have established a role for estrogen in regulating renin-angiotensin system (RAS) expression and activity [18][19][20][21][22][23][24][25][26][27][28]. The identification of angiotensin-converting enzyme-2 (ACE2) as the host cell receptor for the SARS-CoV-1 and SARS-CoV-2 [29] coronaviruses has brought attention to the functions of this enzyme outside the domain of its now established role in modulating angiotensin II (Ang II) metabolism as part of the RAS [30].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated from the heart using the RNeasy Lipit Tissue Mini Kit (Qiagen, Inc., Germantown, MD) and further purified using RNeasy MinElute Cleanup Kit (Qiagen, Inc., Germantown, MD) followed by quality assessment on an Agilent 2100 bioanalyzer, as described previously (18, 19). Relative quantification of mRNA levels by real-time qPCR for ACE, angiotensin converting enzyme 2 (ACE2), mast cell proteases (MCP-1, and MCP-5) was performed using a SYBR Green PCR kit (Qiagen, Inc., Germantown, MD) (19).…”
Section: Methodsmentioning
confidence: 99%